Harmonic grounding impedance of rods in horizontally stratified soils using ABCD-matrix approach - de Araújo, Anderson R.J. (2023)
Grounding electrodes play a fundamental role in the operation of power systems. In this context, precise computation of grounding impedance must consider the frequency-dependence of the soil parameters and the ground organized in stratified layers of soil. This paper proposes an ABCD matrix approach to compute the harmonic grounding impedance of rods buried in frequency-dependent stratified soils directly in the frequency domain. This technique is based on the traditional ABCD matrix used for overhead multi-phase transmission lines extended to grounding systems. In this approach, each rod segment is modeled as a short transmission line where the equivalent harmonic grounding impedance is calculated. Then, the Ground Potential Rise (GPR) waveforms are computed by lightning currents injected into the rods buried in different scenarios. Results indicated that the ABCD matrix approach has shown a good agreement with those obtained using a full-wave electromagnetic software FEKO. The frequency-dependence of the soil electrical parameters causes a significant modification in the harmonic impedance of grounding rods which reduces the GPR peaks considerably, being this reduction more pronounced in homogeneous and 2-layer soils. The proposed technique is an attractive tool since that considers the frequency dependence on each layer of soil, with a low computational cost and good accuracy from 100 Hz up to 1 MHz.